Training on the Utilization of Bada Fruit Innovation to Become a Functional Instant Drink as an Immune System Enhancer in the village of Teluk Majelis - Uce Lestari; Darma Satria; Sri Setiawati; R Ratnawita (Salus Publica: Journal of Community Service, 2023)
The pedada fruit (Sonneratia caseolaris) tastes sour and has a distinctive pedada aroma, as well as a soft fruit texture, so it can be processed into several food products such as jenang, lunkhead, jam and syrup, but its development into an instant antioxidant and immune system boosting drink has not been processed yet. utilized. The highest content of vitamin C in broiler makes it taste sour and unpleasant to eat directly. To overcome this, an innovative functional instant drink powder with added sugar was created. This PPM aims to process pedada fruit which is often found and wasted in Teluk Majelis Village into effective innovations such as instant drinks, jelly candy, marshmallows and can open jobs. The method in this PPM includes counseling related to the benefits and nutritional content of bacada fruit as well as demonstrations on making pedada instant drinks, jelly candies and pedada marshmallows. The PPM results obtained pedada instant drink products, pedada jelly candies and pedada marshmallows which will be made into superior products in Teluk Majelis Village, Kuala Jambi, Tanjung Jabung Timur. From the results of monitoring and evaluation of PPM activities, it was found that the UMKM of Teluk Majelis Village had produced jelly candy and chest marshmallows and had been introduced through the Birthday Expo of East Tanjung Jabung Regency and had become the flagship product of Teluk Majelis Village which was useful as an immune system booster during the Covid-19 pandemic